2008
DOI: 10.1038/npp.2008.199
|View full text |Cite
|
Sign up to set email alerts
|

The Dopamine D2 Receptors in High-Affinity State and D3 Receptors in Schizophrenia: A Clinical [11C]-(+)-PHNO PET Study

Abstract: The dopamine D 2 receptors exist in two states: a high-affinity state (D 2 high ) that is linked to second messenger systems, is responsible for functional effects, and exhibits high affinity for agonists; and a low-affinity state that is functionally inert and exhibits lower affinity for agonists. The dopamine D 3 receptors have high-affinity for agonist (eg dopamine) and the existence of the two affinity states is controversial. Although preclinical studies in animal models of psychosis have shown a selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 43 publications
2
75
1
Order By: Relevance
“…In an attempt to solve this problem, we compared the present BP ND values with baseline (resting) BP ND data from a previous study in patients with schizophrenia. 63 We found no significant difference between the baseline BP ND reported in our previous study 19 and the ones observed under cognitive activation in the present study in all of the ROIs tested (group F 1,19 = 0.735, p = 0.40; region F 4,16 = 21.821, p < 0.001; group × region F 4,16 = 1.014, p = 0.43). In addition, the lack of difference in [ 11 C]-(+)-PHNO binding among the groups may reflect the small DA releasing effect of this particular cognitive task or the lack of participants' own resting state baselines, which may have translated into a statistically nonsignificant difference among the groups.…”
Section: Limitationscontrasting
confidence: 37%
See 2 more Smart Citations
“…In an attempt to solve this problem, we compared the present BP ND values with baseline (resting) BP ND data from a previous study in patients with schizophrenia. 63 We found no significant difference between the baseline BP ND reported in our previous study 19 and the ones observed under cognitive activation in the present study in all of the ROIs tested (group F 1,19 = 0.735, p = 0.40; region F 4,16 = 21.821, p < 0.001; group × region F 4,16 = 1.014, p = 0.43). In addition, the lack of difference in [ 11 C]-(+)-PHNO binding among the groups may reflect the small DA releasing effect of this particular cognitive task or the lack of participants' own resting state baselines, which may have translated into a statistically nonsignificant difference among the groups.…”
Section: Limitationscontrasting
confidence: 37%
“…In agreement with a previous study involving patients with first-episode schizophrenia in a restingstate condition, we found no significant evidence of increased D 2 high or D 3 binding among our study groups. 19 Moreover, to our knowledge, we present the first observations that CHR individuals showed no elevation in D 2 high or D 3 , consistent with the patient population, even while performing a cognitive task. The present results are also corroborated by voxelwise analysis.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Overall, these results are suggestive of a decline in DRD3 binding with age, in particularly among ADP. No previous [ 11 C]PHNO study has reported a relationship between age and DRD2/3 binding (Boileau et al, 2009;Boileau et al, 2012;Ginovart et al, 2007a;Graff-Guerrero et al, 2009a;Graff-Guerrero et al, 2009b;Shotbolt et al, 2012a;Willeit et al, 2006), which could be due to the narrower age range in their reports and/or to the effect of alcohol.…”
Section: D3 Receptors In Alcoholismmentioning
confidence: 65%
“…Although the etiology of schizophrenia is unclear, there is evidence supporting genetic, environmental, and developmental vulnerabilities to disease [1][2][3][4][5][6]. Current evidence supports two main theories regarding the pathophysiology of schizophrenia, which are the glutamate and dopamine hypotheses [7][8][9].…”
Section: Introductionmentioning
confidence: 99%